A new genus and species of Eumolpinae (Coleoptera: Chrysomelidae) from the western dry forest of Ecuador - Flowers, R. Wills (Zootaxa, 2009)
Australotymnes jipijapa new genus, new species (type locality: Ecuador) is described. Adults were collected from vegetation during the rainy season in disturbed and converted dry forest in western Ecuador.